Suatu analisa pilihanraya umum'86 - Zakry Abadi, 1941- (Kuala Lumpur : Syarikat Grafikset Abadi, 1986)
Analysis of the 1986 general election in Malaysia.
In Malay.
Mengandungi indeks.
Keywords: Elections -- Malaysia; Malaysia -- Politics and government